Penggunaan Media Visual Kartu untuk Meningkatkan Penguasaan Kosa Kata Bahasa Arab Siswa Kelas X Agama Madrasah Aliyah Negeri 1 Gresik - Choirul Jamroni (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
This research was motivated by the problem of learners still having difficulty in memorizing Arabic vocabulary. Learners are crowded themselves, the concentration of learning is less and the lack of use of interesting learning media, especially in Arabic vocabulary materials, which results in the ability to memorize the vocabulary of learners is low. To address the problem, the researcher is interested in using the mufrodat card media. The formulation of the problem in this study is